Validity and reliability of different smartphones applications to measure HRV during short and ultra-short measurements in elite athletes. (April 2022) - Moya-Ramon, M.; Mateo-March, M; Peña-González, I.; Zabala, M.; Javaloyes, A.
Highlights: Elite HRV and Welltory are valid and reliable smartphone applications and can be used to monitor HRV in elite endurance athletes. Monitoring of the stress and recovery process is crucial in the population of elite endurance athletes. The HRV use implemented in friendly technology like smartphone applications can substantially increase the compliance of this population. Abstract: Background and objective: Heart rate variability (HRV) has been proposed as a useful marker that can show the performance adaptation and optimize the training process in elite athletes. The development of wearable technology permits the measurement of this marker through smartphone applications. The purpose of this study is to assess the validity and reliability of short and ultra-short HRV measurements in elite cyclists using different smartphone applications. Method: Twenty-six professional cyclists were measured at rest in supine and in seated positions through the simultaneous use of an electrocardiogram and two different smartphone applications that implement different technologies to measure HRV: Elite HRV (with a chest strap) and Welltory (photoplethysmography). Level of significance was set at p < 0.05. Results: Compared to an electrocardiogram, Elite HRV and Welltory showed no differences neither in supine nor in seated positions ( p > 0.05) and they showed very strong to almost perfect correlation levels ( r = 0.77 to 0.94). Furthermore, no differences were found between short (5 min) and ultra-short (1 min) length measurements. Intraclass correlation coefficient showed good to excellent reliability and the standard error of measurement remained lower than 6%. Conclusion: Both smartphone applications can be implemented to monitor HRV using short- and ultra-short length measurements in elite endurance athletes.